A battery balancing control strategy for industrial applications. (12th August 2022) - Liu, Zhenyu; Fan, Zhiguo; Li, Ke; Shao, Xiaoyuan; Fan, Binning; Liu, Aifeng; Yan, Lijun
Abstract: The voltage-based equalization strategy is very simple, and it is widely used in industrial applications; however, for the traditional control strategy, while the battery voltages are equal, the battery management system will stop balancing, due to the complex composition of the battery voltage, the battery cell is not well balanced. This paper proposed a battery balancing control strategy for industrial applications, which adds ohmic voltage compensation based on the traditional equalization control strategy, by increasing the compensation and prolonging the equalization time of the battery cell, a better equalization effect can be achieved. Compared with the traditional equalization strategy, the only parameters required are equalization current and battery internal resistance, these parameters are very easy to obtain without any burden, and are very suitable for industrial applications. This paper analyzes in detail the reasons why the traditional equilibrium strategy is insufficient, introduces the principle and error of the proposed strategy and compares it with the traditional equilibrium strategy. The experimental results show that the error of the equalization strategy proposed in this paper is about 3 mV (discharge) and 2 mV (idle), while the traditional strategy is 10 mV and 8 mV, respectively.